The Discourse on the “Dangerous Child Welfare Parent”—How Contact with Parents Is Constructed as a Risk for Children Under Public Care in Norway - Hilde Anette Aamodt; Marianne Buen Sommerfeldt (Social Sciences)
This article discusses contact and interaction between children, siblings and parents after a care order. We have collected and analyzed audio recordings of discussions between child welfare employees in Norway. In these meetings, the employees discuss and decide the extent and organization of visits and contact between parents and children under public care. Visitation mainly emerges as a risk in the discussions and thus as something that must be limited. This article shows how this risk can be seen in the context of a political or moral discourse in which these parents are given an identity and a position as “dangerous”. However, there are some exceptions. In these exceptions, parents emerge as significant and important, and contact is seen as an opportunity for the child. Here, it is the risk of not having contact that stands out.